2007
DOI: 10.1016/j.cub.2007.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step Acquisition of the Gibberellin-DELLA Growth-Regulatory Mechanism during Land-Plant Evolution

Abstract: Angiosperms (flowering plants) evolved relatively recently and are substantially diverged from early land plants (bryophytes, lycophytes, and others [1]). The phytohormone gibberellin (GA) adaptively regulates angiosperm growth via the GA-DELLA signaling mechanism [2-7]. GA binds to GA receptors (GID1s), thus stimulating interactions between GID1s and the growth-repressing DELLAs [8-12]. Subsequent 26S proteasome-mediated destruction of the DELLAs promotes growth [13-17]. Here we outline the evolution of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
201
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(213 citation statements)
references
References 39 publications
9
201
1
2
Order By: Relevance
“…7): The common ancestor of basal land plants before the separation of the mosses had GAMYB-mediated regulation in the proto-tapetal cells (spore sac cells) and spores for spore outer wall formation. At this stage, the GAMYB-mediated regulation of spore outer wall formation was independent of the GA signalling pathway, as the GA signalling pathway had not yet been established 13,14 . Consistent with this hypothesis, it is reported that the disruption of multiple DELLA-like genes in P. patens did not affect the plant's life cycle 14 , and that the disruption of PpCPS/KS, which encodes ent-kaurene synthase, an enzyme essential for GA synthesis in flowering plants, did not result in abnormal spore development 36 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…7): The common ancestor of basal land plants before the separation of the mosses had GAMYB-mediated regulation in the proto-tapetal cells (spore sac cells) and spores for spore outer wall formation. At this stage, the GAMYB-mediated regulation of spore outer wall formation was independent of the GA signalling pathway, as the GA signalling pathway had not yet been established 13,14 . Consistent with this hypothesis, it is reported that the disruption of multiple DELLA-like genes in P. patens did not affect the plant's life cycle 14 , and that the disruption of PpCPS/KS, which encodes ent-kaurene synthase, an enzyme essential for GA synthesis in flowering plants, did not result in abnormal spore development 36 .…”
Section: Discussionmentioning
confidence: 98%
“…At this stage, the GAMYB-mediated regulation of spore outer wall formation was independent of the GA signalling pathway, as the GA signalling pathway had not yet been established 13,14 . Consistent with this hypothesis, it is reported that the disruption of multiple DELLA-like genes in P. patens did not affect the plant's life cycle 14 , and that the disruption of PpCPS/KS, which encodes ent-kaurene synthase, an enzyme essential for GA synthesis in flowering plants, did not result in abnormal spore development 36 . In the next step, the common ancestor of basal vascular plants before the separation of the lycopsids acquired GA biosynthesis and GA signalling pathways to regulate the pre-existing GAMYB-mediated system, leading to the establishment of the GA signalling pathway via GAMYB.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations